Studi Bibliometrik Topik Riset Task Technology Fit dalam Menunjang Kinerja - Kusuma, Arlan Budi; Fauzi, Achmad (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Task technology fit is a phase where the employee's needs through a long-term career are in accordance with the actual results experienced during work. The aim of this research is (1) to analyze the development of task technology fit and performance research in the last 10 years which has been carried out (2) to analyze the theoretical and empirical contributions provided by task technology fit and performance research. (3) recommending areas for further research. This research was carried out by searching through the Scopus database from Publish or Perish /PoP. The search produced 29 journal articles related to the topic to be discussed. The second stage is to verify the articles collected. During verification, 20 articles were selected and deemed appropriate to the research topic, then this number was narrowed down again and 20 articles remained that were truly relevant to the topic to be discussed in this research. The results of the analysis show that the dominant themes discussed by previous research are related to the themes. The dominant themes discussed by previous research are related to the themes of health service clusters, technology acceptance, academic performance, e-learning, banking services, and TTF results. The theoretical contribution provided by research on task technology fit is related to performance, showing that task technology fit really supports the performance of both employee performance in the organization and consumer performance in using technology. Further research is also needed to identify relevant constructs and indicators that can be used to determine the performance and integration of TTF with other technology use frameworks such as TAM. TTF testing also needs to be carried out in organizational contexts where technology is not used mandatory and focuses on less educated and older workers, because they are generally difficult to be impacted by technological changes.